Supported Fe-MOF catalytic material as well as preparation method and application thereof

The loaded Fe-MOF catalytic materials were prepared by solvent thermal synthesis and ultrasonic impregnation, which solved the problems of equipment corrosion, complex process and poor product stability in traditional concentrated sulfuric acid catalytic processes, and achieved efficient and safe synthesis of ethylparaben.

CN119771501APending Publication Date: 2025-04-08SHAANXI COAL & CHEM TECH INST
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411790553.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The synthesis of ethylparaben esters in traditional concentrated sulfuric acid catalytic process has problems such as equipment corrosion, complex process, poor safety and poor product stability.

Method used

The Fe-MOF material was synthesized by solvothermal synthesis, and the active catalyst aid was loaded onto the Fe-MOF material by ultrasonic impregnation to obtain a supported Fe-MOF catalytic material.

Benefits of technology

It improves the load uniformity and catalytic activity of the catalyst, simplifies the process flow, reduces production costs, and achieves efficient and safe synthesis of ethylparaben.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a supported Fe-MOF catalytic material as well as a preparation method and application thereof, and belongs to the technical field of ethylparaben catalysis. The invention discloses a preparation method, which comprises the following steps: taking substituted terephthalic acid as a bridging ligand, providing metal ions by using an inorganic salt containing Fe < 3 + >, synthesizing a Fe-MOF material by using a solvothermal synthesis method, and then self-assembling and loading an active catalytic promoter on the Fe-MOF material by using ultrasonic assistance to finally obtain the loaded Fe-MOF catalytic material. The catalyst is high in catalytic efficiency, can be recycled, is low in alcohol-acid ratio in an esterification reaction process, is high in raw material conversion rate, is high in product purity, is high in yield, is pollution-free, and can effectively solve the problems of a traditional process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ethyl paraben catalysis, and in particular relates to a supported Fe-MOF catalytic material and a preparation method and application thereof. Background Art

[0002] Ethyl paraben (or ethyl p-hydroxybenzoate) is a commonly used water-soluble preservative, widely used in the fields of medicine, cosmetics, food, etc. Its main characteristics are safety, high efficiency, and broad-spectrum antibacterial. At present, the main industrial production method is to use p-hydroxybenzoic acid and ethanol as raw materials, concentrated sulfuric acid as a catalyst, and promote the esterification reaction to synthesize ethyl paraben by adding a water-carrying agent for azeotropic water separation. Then it has to go through multiple processes such as alkalization, concentration, water washing, crystallization, centrifugal washing, etc. to obtain the product. This process uses concentrated sulfuric acid as a catalyst, so there are defects such as equipment corrosion, high three wastes, complex process, poor safety, etc. At the same time, product color, crystal form, purity and other indicators are often unstable.

[0003] In order to solve the many problems existing in the traditional concentrated sulfuric acid catalytic esterification process for the synthesis of ethyl paraben, people are committed to developing high-performance supported catalysts to replace sulfuric acid, such as loading acidic active substances onto inorganic carrier materials such as silica, alumina or molecular sieves to further improve their catalytic performance. Since inorganic material carriers often have limitations in crystalline structure regulation and easy loss of immobilized active components, the performance optimization of supported catalysts for esterification reactions is limited. MOF materials, as a new type of metal-organic framework material, have higher chemical stability and more flexible controllability, which can make up for the natural defects of inorganic material carriers. For example, Fe-MOF materials have been widely studied due to their good properties and chemical diversity. However, traditional supported Fe-MOF materials are often synthesized by medium- and high-pressure hydrothermal methods, followed by separation and purification, and then loaded with active substances by impregnation. The overall synthesis process is complicated, the preparation cost is high, the loaded components are single and the uniformity is poor, and they are rarely used in the field of esterification reactions. Therefore, it will have good application prospects to develop efficient supported Fe-MOF material catalysts, explore their economically feasible synthesis processes, and apply them to the synthesis of ethyl paraben to replace the traditional concentrated sulfuric acid catalytic process. Summary of the invention

[0004] The purpose of the present invention is to provide a supported Fe-MOF catalytic material and a preparation method and application thereof, which are helpful to solve the technical problem of poor loading uniformity of traditional esterification reaction supported catalysts.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention discloses a method for preparing a supported Fe-MOF catalytic material, comprising the following steps: To replace the terephthalate bridging ligand and Fe3+ The inorganic salts were used as raw materials to synthesize Fe-MOF materials by solvothermal synthesis. Subsequently, the active catalytic promoter is self-assembled and loaded onto the Fe-MOF material, and finally the supported Fe-MOF catalytic material is obtained after post-treatment.

[0006] Further, the terephthalic acid bridging ligand and the Fe-containing 3+ The specific steps of synthesizing Fe-MOF materials by solvent thermal synthesis method are as follows: Substituted terephthalate bridging ligand and Fe 3+ The inorganic salt is dissolved in a solvent to obtain a mixed solution; the mixed solution is then heated to react, and after the reaction is completed, the Fe-MOF material is obtained.

[0007] Furthermore, the heating temperature is 60-100° C., and the reaction time is 1-3 hours.

[0008] Furthermore, in the mixed solution, the concentration of the substituted terephthalic acid bridging ligand is 0.1 to 1 mol / L; The substituted terephthalic acid bridging ligand is one of terephthalic acid, 2-aminoterephthalic acid, 2-nitroterephthalic acid, 2-bromoterephthalic acid and 2,3,5,6-tetramethylterephthalic acid; The Fe-containing 3+ The inorganic salt is one or more of Fe2(SO4)3, FeCl3, Fe(NO3)3, FePO4 and Fe(CF3SO3)3; The solvent is one or more of methanol, ethanol, isopropanol, acetonitrile, N,N-dimethylformamide and N,N-dimethylacetamide.

[0009] Furthermore, the Fe-containing 3+ The molar ratio of the inorganic salt and the substituted terephthalic acid bridging ligand is (1-2.5):1.

[0010] Furthermore, the method used for self-assembly loading the active catalyst promoter onto the Fe-MOF material is ultrasonic impregnation; The ultrasonic immersion method has an ultrasonic frequency of 25 to 60 kHz, a temperature of 50 to 80° C., and a time of 1 to 3 hours.

[0011] Furthermore, the mass ratio of the active catalyst promoter to the substituted terephthalic acid bridging ligand is (0.1-0.6):1; The active catalyst promoter is N[CH2PO(OH)2]3, NH2SO3H, ClSO3H, C 12 H 27PO3, H3PO4·12MoO3, H3O40PW 12 One of xH2O, PPA and H2WO4.

[0012] Further, the post-treatment includes filtering, washing and drying treatments performed in sequence; The drying process is carried out at a temperature of 100 to 160° C. and for a time of 0.5 to 1.5 h.

[0013] The invention also discloses a supported Fe-MOF catalytic material prepared by the preparation method.

[0014] The present invention also discloses the use of the above-mentioned supported Fe-MOF catalytic material in the synthesis reaction of ethyl paraben, comprising the following steps: Using p-hydroxybenzoic acid and ethanol as raw materials, an esterification reaction is carried out under the catalytic action of the supported Fe-MOF catalytic material to obtain ethyl paraben. Wherein, the molar ratio of ethanol to p-hydroxybenzoic acid is (1.0-5.0):1.0; The amount of the supported Fe-MOF catalyst material is 0.1 wt.% to 10.0 wt.% of p-hydroxybenzoic acid; The reaction temperature of the esterification reaction is 60°C to 120°C, and the reaction time is 1 to 10 hours.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a method for preparing a supported Fe-MOF catalytic material, wherein terephthalic acid is used as a bridging ligand, and Fe 3+ The Fe-MOF material is synthesized by solvent thermal synthesis method using inorganic salts to provide metal ions, and then the active catalyst promoter is self-assembled and loaded on the Fe-MOF material with the assistance of ultrasound, and finally a supported Fe-MOF catalytic material is obtained; this method uses the normal pressure solvent thermal method to synthesize the Fe-MOF catalytic material, making the overall process safer and more operable. At the same time, the catalyst promoter is loaded on the Fe-MOF material with the assistance of ultrasound, which improves the loading efficiency of the traditional impregnation method and improves the overall uniformity of the catalyst promoter loading.

[0016] The present invention also discloses a supported Fe-MOF catalytic material prepared by the above method. Active additives such as sulfonic acid and phosphoric acid are ultrasonically assisted to impregnate onto the Fe-MOF carrier to synthesize a supported Fe-MOF material catalyst, further exploring the catalytic activity potential of the sulfonic acid and phosphoric acid active substances, enriching the active sites and making the active components evenly distributed. The prepared catalyst has regular crystal structure, the supported components are not easily lost, and the overall catalytic activity is improved.

[0017] The present invention also discloses the application of the supported Fe-MOF catalytic material in the synthesis reaction of ethyl paraben. The catalyst has high catalytic efficiency and can be recycled. The esterification reaction process has a low alcohol-acid ratio, a high raw material conversion rate, a high product purity, a high yield, and no pollution, which can effectively solve the problems existing in traditional processes. DETAILED DESCRIPTION

[0018] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0019] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0020] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0021] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0022] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0023] The present invention provides a method for preparing a supported Fe-MOF catalytic material, comprising the following steps: Substituted terephthalic acid as the bridging ligand, containing Fe 3+ The inorganic salt provides metal ions, and the Fe-MOF material is synthesized by the solvent thermal synthesis method. Then, the active catalytic promoter is self-assembled and loaded on the Fe-MOF material by ultrasonic impregnation method. After filtration, washing and drying, the supported Fe-MOF esterification reaction catalyst is obtained.

[0024] Preferably, the substituted terephthalic acid as the bridging ligand is one of terephthalic acid, 2-aminoterephthalic acid, 2-nitroterephthalic acid, 2-bromoterephthalic acid, and 2,3,5,6-tetramethylterephthalic acid.

[0025] Preferably, Fe 3+ The inorganic salts include one or more of Fe2(SO4)3, FeCl3, Fe(NO3)3, FePO4 and Fe(CF3SO3)3.

[0026] Preferably, the solvent includes one or more of methanol, ethanol, isopropanol, acetonitrile, N,N-dimethylformamide, and N,N-dimethylacetamide.

[0027] Preferably, the active catalyst promoter includes: N[CH2PO(OH)2]3, NH2SO3H, ClSO3H, C 12 H 27 PO3, H3PO4·12MoO3, H3O 40 PW 12 One of xH2O, PPA ((P2O5)%≥85%) and H2WO4.

[0028] Preferably, Fe 3+ The molar ratio of the inorganic salt and the substituted terephthalic acid bridging ligand is (1-2.5):1.

[0029] Preferably, the concentration of the substituted terephthalic acid bridging ligand in the solvothermal method is 0.1 to 1 mol / L.

[0030] Preferably, the mass ratio of the active catalyst promoter to the substituted terephthalic acid bridging ligand is (0.1-0.6):1.

[0031] Preferably, the temperature for synthesizing Fe-MOF material by solvothermal method is 60-100° C. and the time is 1-3 h.

[0032] Preferably, the ultrasonic frequency of the supported Fe-MOF catalyst synthesized by ultrasonic impregnation is 25 to 60 kHz, the temperature is 50 to 80° C., and the time is 1 to 3 h.

[0033] Preferably, the supported Fe-MOF catalyst is dried at a temperature of 100 to 160 degrees for a time of 0.5 to 1.5 hours.

[0034] The present invention also discloses the use of the supported Fe-MOF catalyst as a catalyst for synthesizing ethyl paraben, comprising the following steps: With p-hydroxybenzoic acid and ethanol as raw materials, an esterification reaction is carried out under the catalytic action of the supported Fe-MOF catalyst to obtain ethyl paraben.

[0035] Preferably, the molar ratio of ethanol to p-hydroxybenzoic acid is 1.0-5.0:1.0.

[0036] Preferably, the amount of the supported Fe-MOF catalyst used is 0.1 wt.% to 10.0 wt.% of p-hydroxybenzoic acid.

[0037] Preferably, the reaction temperature of the esterification reaction is 60° C. to 120° C., and the reaction time is 1 to 10 hours.

[0038] Preferably, the reaction device used in the method includes a high-pressure reactor with a heat exchanger and an ethanol recovery tank.

[0039] Preferably, the gas released after the reaction is completed is condensed by a heat exchanger and then enters an ethanol recovery tank for recovery; after the reaction is completed, the catalyst is filtered out by hot filtration, and the filtrate is concentrated, recrystallized, filtered, and dried to obtain the ethyl paraben product.

[0040] The supported Fe-MOF catalyst used in the present invention has a simple preparation process, excellent catalytic performance and can be recycled and reused, which reduces the generation of three wastes in the production process, improves the overall safety of the reaction process, and is a green and environmentally friendly process.

[0041] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0042] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0043] Example 1 A method for preparing a supported Fe-MOF catalytic material comprises the following steps: Weigh 10.0 g of 2-aminoterephthalic acid and 24.3 g of Fe2(SO4)3, add them into a beaker containing 150 mL of methanol, heat to 60 °C and react for 2.0 h to obtain Fe-MOF material; Subsequently, 34.5 g of active auxiliary agent N[CH2PO(OH)2] was added, and the reaction was carried out under an ultrasonic environment of 30 kHz and 60°C for 1.5 h. Finally, the temperature was cooled to room temperature, and the light red solid was filtered out. The solid was rinsed twice with methanol and dried in a vacuum at 110°C for 2.0 h to obtain a supported Fe-MOF catalytic material (ATMP(45%)@Fe-MOF).

[0044] Example 2 A method for preparing a supported Fe-MOF catalytic material comprises the following steps: Weigh 10.0 g of 2-aminoterephthalic acid and 24.3 g of Fe2(SO4)3, add them into a beaker containing 150 mL of N,N-dimethylacetamide, heat to 80 °C and react for 2.0 h to obtain Fe-MOF material; Subsequently, 35.0 g of active auxiliary agent N[CH2PO(OH)2] was added, and the reaction was carried out under an ultrasonic environment of 40 kHz and 80°C for 1.5 h. Finally, the temperature was cooled to room temperature, and the light red solid was filtered out. The solid was rinsed twice with N,N-dimethylacetamide and dried in a vacuum at 160°C for 2.0 h to obtain a supported Fe-MOF catalytic material (ATMP(50%)@Fe-MOF).

[0045] Example 3 A method for preparing a supported Fe-MOF catalytic material comprises the following steps: Weigh 10.0 g of terephthalic acid and 14.8 g of Fe(CF3SO3)3, add them into a beaker containing 200 mL of DMF, heat to 100 °C and react for 2.0 h to obtain Fe-MOF material; Then add the active agent H3O 40 PW 12 .xH2O 5.0g, and reacted under ultrasonic environment of 40kHZ and 80℃ for 2h. Finally, the temperature was cooled to room temperature to filter out the brown-red solid, which was rinsed twice with DMF and dried in vacuum at 160℃ for 2.0h to obtain the supported Fe-MOF catalytic material (PTA(50%)@Fe-MOF).

[0046] Example 4 A method for preparing a supported Fe-MOF catalytic material comprises the following steps: Weigh 10.0 g of terephthalic acid and 16.1 g of Fe(CF3SO3)3, add them into a beaker containing 200 mL of DMF, heat to 80 °C and react for 2.0 h to obtain Fe-MOF material; Subsequently, 4.5 g of active auxiliary agent PPA was added, and the reaction was carried out under an ultrasonic environment of 40 kHz and 80°C for 2 h. Finally, the temperature was cooled to room temperature, and the brown-red solid was filtered out. The solid was rinsed twice with DMF and dried in a vacuum at 160°C for 2.0 h to obtain a supported Fe-MOF catalytic material (PPA (45%)@Fe-MOF).

[0047] Example 5 A method for preparing a supported Fe-MOF catalytic material comprises the following steps: Weigh 10.0 g of 2,3,5,6-tetramethylterephthalic acid and 11.0 g of FeCl3, add them into a beaker containing 150 mL of acetonitrile, heat to 80 °C and react for 2.0 h to obtain Fe-MOF material; Subsequently, 5.0 g of active additive PPA was added, and the reaction was carried out under an ultrasonic environment of 40 kHz and 80°C for 2 h. Finally, the temperature was cooled to room temperature, and the brown solid was filtered out. The solid was rinsed twice with acetonitrile and dried in a vacuum at 120°C for 2.0 h to obtain a supported Fe-MOF catalytic material (PPA (50%) @Fe-MOF).

[0048] Example 6 A method for preparing a supported Fe-MOF catalytic material comprises the following steps: Weigh 10.0 g of 2-nitroterephthalic acid and 12.7 g of Fe(CF3SO3)3, add them into a beaker containing 150 mL of DMF, heat to 80 °C and react for 2.0 h to obtain Fe-MOF material; Subsequently, 4.5 g of active auxiliary agent H3PO4·12MoO3 was added, and the reaction was carried out under an ultrasonic environment of 40 kHz and 80°C for 2.0 h. Finally, the temperature was cooled to room temperature, the brown solid was filtered out, rinsed twice with acetonitrile and dried in a vacuum at 160°C for 2.0 h to obtain a supported Fe-MOF catalytic material (PMA (45%)@Fe-MOF).

[0049] Application Example 1 The supported Fe-MOF catalytic material in Example 1 was added according to 5.0wt.% of the mass of p-hydroxybenzoic acid, and the molar ratio of p-hydroxybenzoic acid to ethanol was 1:3.5. The reaction kettle was added, and after purging with N2 to remove the air, the reaction was stirred at 80°C and 500r / min for 3h, and the catalyst was removed by hot filtration to obtain a reaction solution; liquid chromatography was used for analysis, and the results showed that the conversion rate of p-hydroxybenzoic acid was 58%, and the selectivity of ethylparaben was 99%; the reaction solution was concentrated, recrystallized, filtered, washed, and dried to obtain the product ethylparaben, and the product yield was 52% and the purity was 99%.

[0050] Application Example 2 The supported Fe-MOF catalytic material in Example 1 was added according to 10.0wt.% of the mass of p-hydroxybenzoic acid, and the ratio of the amount of p-hydroxybenzoic acid to ethanol was 1:5. After being purged with N2 to remove air, the reaction was stirred at 100°C and 500r / min for 5h, and the catalyst was removed by hot filtration to obtain a reaction solution; the result of analysis by liquid chromatography was that the conversion rate of p-hydroxybenzoic acid was 87% and the selectivity of ethylparaben was 99%. The reaction solution was concentrated, recrystallized, filtered, washed, and dried to obtain the product ethylparaben, with a product yield of 81% and a purity of 99%.

[0051] Application Example 3 The supported Fe-MOF catalytic material in Example 2 was added according to 2.0wt.% of the mass of p-hydroxybenzoic acid, and the molar ratio of p-hydroxybenzoic acid to ethanol was 1:3.0. The reaction kettle was added, and after purging with N2 to remove the air, the reaction was stirred at 100°C and 500r / min for 5h, and the catalyst was removed by hot filtration to obtain a reaction solution; liquid chromatography was used for analysis, and the results showed that the conversion rate of p-hydroxybenzoic acid was 76%, and the selectivity of ethylparaben was 99%; the reaction solution was concentrated, recrystallized, filtered, washed, and dried to obtain the product ethylparaben, and the product yield was 71% and the purity was 99%.

[0052] Application Example 4 The supported Fe-MOF catalytic material in Example 2 was added according to 5.0wt.% of the mass of p-hydroxybenzoic acid, and the molar ratio of p-hydroxybenzoic acid to ethanol was 1:5. The reaction kettle was added, and after purging with N2 to remove the air, the reaction was stirred at 100°C and 500r / min for 5h, and the catalyst was removed by hot filtration to obtain a reaction solution; liquid chromatography was used for analysis, and the results showed that the conversion rate of p-hydroxybenzoic acid was 94%, and the selectivity of ethylparaben was 99%; the reaction solution was concentrated, recrystallized, filtered, washed, and dried to obtain the product ethylparaben, and the product yield was 90% and the purity was 99%.

[0053] Application Example 5 The supported Fe-MOF catalytic material in Example 3 was added according to 5.0wt.% of the mass of p-hydroxybenzoic acid, and the molar ratio of p-hydroxybenzoic acid to ethanol was 1:4. The reaction kettle was added, and after purging with N2 to remove air, the reaction was stirred at 120°C and 500r / min for 5h, and the catalyst was removed by hot filtration to obtain a reaction solution; liquid chromatography was used for analysis, and the results showed that the conversion rate of p-hydroxybenzoic acid was 98%, and the selectivity of ethylparaben was 99%; the reaction solution was concentrated, recrystallized, filtered, washed, and dried to obtain the product ethylparaben, and the product yield was 94% and the purity was 99%.

[0054] Application Example 6 The supported Fe-MOF catalytic material in Example 4 was added according to 3.0wt.% of the mass of p-hydroxybenzoic acid, and the molar ratio of p-hydroxybenzoic acid to ethanol was 1:4.0. The reaction kettle was added, and after purging with N2 to remove air, the reaction was stirred at 110°C and 500r / min for 5h. The catalyst was removed by hot filtration to obtain a reaction solution. Liquid chromatography was used for analysis, and the results showed that the conversion rate of p-hydroxybenzoic acid was 89% and the selectivity of ethylparaben was 99%. The reaction solution was concentrated, recrystallized, filtered, washed, and dried to obtain the product ethylparaben, and the product yield was 85% and the purity was 99%.

[0055] Application Example 7 The supported Fe-MOF catalytic material in Example 4 was added according to 5.0wt.% of the mass of p-hydroxybenzoic acid, and the molar ratio of p-hydroxybenzoic acid to ethanol was 1:5.0. The reaction kettle was added, and after purging with N2 to remove air, the reaction was stirred at 110°C and 500r / min for 5h, and the catalyst was removed by hot filtration to obtain a reaction solution; liquid chromatography was used for analysis, and the results showed that the conversion rate of p-hydroxybenzoic acid was 98%, and the selectivity of ethylparaben was 99%; the reaction solution was concentrated, recrystallized, filtered, washed, and dried to obtain the product ethylparaben, and the product yield was 95% and the purity was 99%.

[0056] Application Example 8 The supported Fe-MOF catalytic material in Example 5 was added according to 5.0wt.% of the mass of p-hydroxybenzoic acid, and the molar ratio of p-hydroxybenzoic acid to ethanol was 1:5.0. The reaction kettle was added, and after purging with N2 to remove air, the reaction was stirred at 110°C and 500r / min for 5h, and the catalyst was removed by hot filtration to obtain a reaction solution; liquid chromatography was used for analysis, and the results showed that the conversion rate of p-hydroxybenzoic acid was 93%, and the selectivity of ethylparaben was 99%; the reaction solution was concentrated, recrystallized, filtered, washed, and dried to obtain the product ethylparaben, and the product yield was 89% and the purity was 99%.

[0057] Comparative Example 1 Comparative Application Example 5, the unloaded active agent H3O 40 PW 12 .xH2O was added at 5.0wt.% of the mass of p-hydroxybenzoic acid, and other materials and reaction conditions were consistent with those in Application Example 5. After the reaction was completed, liquid chromatography was used for analysis, and the results showed that the conversion rate of p-hydroxybenzoic acid was 48%, and the selectivity of ethylparaben was 99%. The reaction solution was concentrated, recrystallized, filtered, washed, and dried to obtain the product ethylparaben, with a product yield of 42% and a purity of 99%.

[0058] Comparative Example 2 Comparative Application Example 7, the unloaded active auxiliary PPA was added according to 5.0wt.% of the mass of p-hydroxybenzoic acid, and the other materials and reaction conditions were consistent with those in Application Example 7. After the reaction was completed, liquid chromatography was used for analysis, and the results showed that the conversion rate of p-hydroxybenzoic acid was 51%, and the selectivity of ethyl paraben was 99%; the reaction solution was concentrated, recrystallized, filtered, washed, and dried to obtain the product ethyl paraben, and the product yield was 46% and the purity was 99%.

[0059] Comparative Example 3 Compared with the traditional concentrated sulfuric acid catalytic esterification process, concentrated sulfuric acid is added according to 5.0wt.% of the mass of p-hydroxybenzoic acid, and the molar ratio of p-hydroxybenzoic acid: ethanol: toluene (with water) is 1.0:5.0:1.0. It is added to a three-necked flask with a water separator (concentrated sulfuric acid is added dropwise), and refluxed for water separation reaction for 5 hours. The results of liquid chromatography analysis showed that the conversion rate of p-hydroxybenzoic acid was 68% and the selectivity of ethyl paraben was 99%; after evaporating the excess solvent, neutralizing with sodium bicarbonate to remove concentrated sulfuric acid and unreacted organic acid, activated carbon + ethanol was added for decolorization, and then filtered, concentrated, recrystallized, filtered, washed, and dried to obtain the product ethyl paraben, with a product yield of 56% and a purity of 99%.

[0060] From the above experimental results, it can be seen that the supported Fe-MOF material synthesized by the "one-pot method" of the present invention has a good catalytic effect in the reaction of synthesizing ethyl paraben from p-hydroxybenzoic acid and ethanol, and the reaction conversion rate and yield can be greatly improved; by comparing Application Example 5 with Comparative Example 1, it can be seen that the active substance H3O 40 PW 12 .After loading with xH2O, the conversion rate and product yield of the reaction are greatly improved; comparing Application Example 7 with Comparative Example 2, after loading the active substance PPA, the reaction conversion rate and yield can be greatly improved; comparing Application Example 7 with the traditional concentrated sulfuric acid catalytic process, under the same addition amount, the catalytic efficiency of the supported Fe-MOF catalyst proposed in the present invention is better than that of sulfuric acid. In addition to avoiding the corrosion of concentrated sulfuric acid to the equipment, there is no need for alkali washing, decolorization and other processes, the process flow is shortened, and the amount of wastewater is greatly reduced, thereby improving the reaction efficiency, reducing the production cost, and meeting the requirements of green technology.

[0061] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a supported Fe-MOF catalytic material, characterized in that: The following steps are involved: To replace the terephthalic acid bridging ligand and Fe 3+ The inorganic salts were used as raw materials to synthesize Fe-MOF materials by solvothermal synthesis. Subsequently, the active catalytic promoter is self-assembled and loaded onto the Fe-MOF material, and finally the supported Fe-MOF catalytic material is obtained after post-treatment.

2. The method for preparing a supported Fe-MOF catalytic material according to claim 1, characterized in that: The terephthalic acid bridging ligand and the Fe-containing 3+ The specific steps of synthesizing Fe-MOF materials by solvent thermal synthesis method are as follows: Substituted terephthalate bridging ligand and Fe 3+ The inorganic salt is dissolved in a solvent to obtain a mixed solution; the mixed solution is then heated to react, and after the reaction is completed, the Fe-MOF material is obtained.

3. A method for preparing a supported Fe-MOF catalytic material according to claim 2, characterized in that: The heating temperature is 60-100° C., and the reaction time is 1-3 hours.

4. A method for preparing a supported Fe-MOF catalytic material according to claim 2, characterized in that: In the mixed solution, the concentration of the substituted terephthalic acid bridging ligand is 0.1 to 1 mol / L; The substituted terephthalic acid bridging ligand is one of terephthalic acid, 2-aminoterephthalic acid, 2-nitroterephthalic acid, 2-bromoterephthalic acid and 2,3,5,6-tetramethylterephthalic acid; The Fe-containing 3+ The inorganic salt is one or more of Fe2(SO4)3, FeCl3, Fe(NO3)3, FePO4 and Fe(CF3SO3)3; The solvent is one or more of methanol, ethanol, isopropanol, acetonitrile, N,N-dimethylformamide and N,N-dimethylacetamide.

5. A method for preparing a supported Fe-MOF catalytic material according to claim 1, characterized in that: The Fe-containing 3 + The molar ratio of the inorganic salt and the substituted terephthalic acid bridging ligand is (1-2.5):

1.

6. A method for preparing a supported Fe-MOF catalytic material according to claim 1, characterized in that: The method for self-assembly loading the active catalyst promoter onto the Fe-MOF material is ultrasonic impregnation; The ultrasonic immersion method has an ultrasonic frequency of 25 to 60 kHz, a temperature of 50 to 80° C., and a time of 1 to 3 hours.

7. A method for preparing a supported Fe-MOF catalytic material according to claim 1, characterized in that: The mass ratio of the active catalyst promoter to the substituted terephthalic acid bridging ligand is (0.1-0.6):1; The active catalyst promoter is N[CH2PO(OH)2]3, NH2SO3H, ClSO3H, C 12 H 27 PO3, H3PO4·12MoO3, H3O40PW 12 One of xH2O, PPA and H2WO4.

8. A method for preparing a supported Fe-MOF catalytic material according to claim 1, characterized in that: The post-treatment includes filtering, washing and drying processes performed in sequence; The drying process is carried out at a temperature of 100 to 160° C. and for a time of 0.5 to 1.5 h.

9. A supported Fe-MOF catalytic material, characterized in that: The method is prepared by any one of claims 1 to 8.

10. The use of the supported Fe-MOF catalytic material according to claim 9 in the synthesis reaction of ethyl paraben, characterized in that: The following steps are involved: Using p-hydroxybenzoic acid and ethanol as raw materials, an esterification reaction is carried out under the catalytic action of the supported Fe-MOF catalytic material to obtain ethyl paraben. Wherein, the molar ratio of ethanol to p-hydroxybenzoic acid is (1.0-5.0):1.0; The amount of the supported Fe-MOF catalyst material is 0.1wt.% to 10.0wt.% of p-hydroxybenzoic acid; The reaction temperature of the esterification reaction is 60°C to 120°C, and the reaction time is 1 to 10 hours.

Citation Information

Cited By

  • Molecularly imprinted metal-organic framework catalysts, their preparation methods and applications

    CN122558550A